Quantitative MRI T2 Mapping is Able to Assess Tissue Quality After Reparative and Regenerative Treatments of Osteochondral Lesions of the Talus. Issue 5 (28th May 2021) - Rizzo, Giulio; Cristoforetti, Alessandro; Marinetti, Alessandro; Rigoni, Marta; Puddu, Leonardo; Cortese, Fabrizio; Nollo, Giandomenico; Della Sala, Sabino W.; Tessarolo, Francesco
Abstract : Background: Quantitative MRI has potential for tissue characterization after reparative and regenerative surgical treatment of osteochondral lesions of the talus (OCLTs). However available data is inconclusive and quantitative sequences can be difficult to implement in real‐time clinical application. Purpose: To assess the potential of T2 mapping in discriminating articular tissue characteristics after reparative and regenerative surgery of OCLTs in real‐world clinical settings. Study Type: Observational and prospective cohort study. Population: 15 OCLT patients who had received either reparative treatment with arthroscopic microfracture surgery (MFS) for a grade I lesion or regenerative treatment with bone marrow derived cell transplantation (BMDCT) for a grade II lesion. Field Strength/Sequence: 1.5 T, proton density weighted TSE, T2‐weighted true fast imaging with steady‐state‐free precession and multi‐echo T2 mapping sequences. Assessment: Patients were evaluated at a minimum postoperative follow‐up of 24 months. T2 maps of the ankle were generated and the distribution of T2 values was analyzed in manually identified volumes of interest (VOIs) for both treated lesions (TX) and healthy cartilage (CTRL). The amount of fibrocartilage, hyaline‐like and remodeling tissue in TX VOIs was obtained, based on T2 thresholds from CTRL VOIs. Statistical Tests: Fisher's exact test for categorical data, nonparametric Mann–Whitney U test for continuous data. The statistical significance level was P < 0.05. Results: From CTRL VOI analysis, T2 < 25 msec, 25 msec ≤ T2 ≤ 45 msec, and T2 > 45 msec were considered as representative for fibrocartilage, hyaline‐like and remodeling tissue, respectively. Tissue composition of the two treatment groups was different, with significantly more fibrocartilage (+28%) and less hyaline‐like tissue (−15%) in MFS than in BMDCT treated lesions. No difference in healthy tissue composition was found between the two groups ( P = 0.75). Data Conclusions: T2 mapping of surgically treated OCLTs can provide quantitative information about the type and amount of newly formed tissue at the lesion site, thereby facilitating surgical follow‐up in a real‐word clinical setting. Level of Evidence: 2 Technical Efficacy: Stage 3